The Sociolinguistics of Academic Publishing : Language and the Practices of Homo Academicus - Salö, Linus (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
'A thoughtful study of the importance of language choice for making scholarly findings known to the world.' - Dr Florian Coulmas, University of Duisburg-Essen, Germany This book presents a sociolinguistics of academic publishing from an historical and contemporary perspective. Using Swedish academia as a case study, it focuses on publishing practices within history and psychology. The author demonstrates how new regimes of research evaluation and performance-based funding are impinging on university life. His central argument, following the French sociologist Bourdieu, is that the trend towards publishing in English should be understood as a social strategy, developed in response to such transformations. Thought-provoking and challenging, this book will interest students and scholars of sociolinguistics, language planning and language policy, research policy, sociology of science, history and psychology.
Keywords: Linguistics.; Applied linguistics.; Scandinavian languages.; Sociolinguistics.; English language.; Language policy.; elektronické knihy; electronic books